PENGENALAN ISI PIRINGKU DENGAN METODE PENDEKATAN SENI GAMBAR DI SMP YARI PADANG - Ade Teti Vani; Irwan Triansyah; Nadia Purnama Dewi; Dessy Abdullah; Aryaldi Zulkarnaini (Yayasan Nusantara Hasana Berdikari, 2024)
Motivation/Background: The contents of Isi Piringku determine the nutritional status of adolescents. The wrong type, and the amount of food will cause malnutrition problems in adolescents. Introduction to the method of drawing art is effective for teenagers because drawing art includes learning to play. This method makes it easier to accept the concept of Fill My Plate. The purpose of the service activity is to provide knowledge about the contents of my plate as the first step in implementing a nutrition-conscious attitude for YARI Padang Junior High School teenagers. Method: The method of service is in the form of counseling and workshops. Counseling is carried out at the beginning and end of service. Workshops in the form of drawing art are given as core activities. Results: The results of dedication were obtained by only 5% of students who just learned about the contents of Isi Piringku. During the workshop 100% of students can analyze the contents of Isi Piringku and at the end of the service, 100% of students can analyze the contents of Isi Piringku. Conclusions: The conclusion of this devotion is that the art of drawing effectively increases the knowledge of the contents of my plate. Furthermore, the devotion of Isi Piringku can be continued with a food workshop Isi Piringku.